An innovative technique for palatal reservoir construction in complete dentures: A case report - K S Bharanija; Ashok V; Anandapandian Ponsekar Abraham (Tabriz University of Medical Sciences, 2018)
The retention and comfort of wearing prosthesis mainly depends on saliva. In reduced saliva conditions, such as xerostomia or radiation therapy, the oral mucosa tends to become dry and ulcerated, leading to the patient's inability to retain the prosthesis. Various techniques have been reported in the literature regarding the use of a reservoir with holes in dentures. The results have not been satisfactory because the flow of the salivary substitute could not be controlled and with frequent cleaning of the denture being necassary to maintain the patency of the reservoir holes. A newer technique for incorporation of a palatal reservoir with controlled artificial salivary flow in complete denture is being explained in this article, which improved the denture retention, comfort, mastication and speech of the patient.